Global, regional, and national burden of migraine in 204 countries and territories, 1990 to 2019. Issue 2 (26th March 2021) - Safiri, Saeid; Pourfathi, Hojjat; Eagan, Arielle; Mansournia, Mohammad Ali; Khodayari, Mohammad Taghi; Sullman, Mark J.M.; Kaufman, Jay; Collins, Gary; Dai, Haijiang; Bragazzi, Nicola Luigi; Kolahi, Ali-Asghar
Abstract : Supplemental Digital Content is Available in the Text. Globally, there were 1 billion prevalent cases, 87.6 million incident cases, and 42.1 million YLDs because of migraine in 2019. Abstract: Data from the Global Burden of Disease Study 2019 were used to report the burden of migraine in 204 countries and territories during the period 1990 to 2019, through a systematic analysis of point prevalence, annual incidence, and years lived with disability (YLD). In 2019, the global age-standardised point prevalence and annual incidence rate of migraine were 14, 107.3 (95% Uncertainty Interval [UI] 12, 270.3-16, 239) and 1142.5 (95% UI 995.9-1289.4) per 100, 000, an increase of 1.7% (95% UI 0.7%-2.8%) and 2.1% (95% UI 1.1%-2.8%) since 1990, respectively. Moreover, the global age-standardised YLD rate in 2019 was 525.5 (95% UI 78.8-1194), an increase of 1.5% (95% UI –4.4% to 3.3%) since 1990. The global point prevalence of migraine in 2019 was higher in females and increased by age up to the 40 to 44 age group, then decreased with increased age. Belgium (22, 400.6 [95% UI: 19, 305.2-26, 215.8]), Italy (20, 337.7 [95% UI: 17, 724.7-23, 405.8]), and Germany (19, 436.4 [95% UI: 16, 806.2-22, 810.3]) had the 3 highest age-standardised point prevalence rates for migraine in 2019. In conclusion, there were large intercountry differences in the burden of migraine, and this burden increased significantly across the measurement period. These findings suggest that migraine care needs to be included within the health system to increase population awareness regarding the probable risk factors and treatment strategies especially among young adults and middle-aged women, as well as to increase the data on migraines.